2015
DOI: 10.1016/j.bjid.2015.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Rare severe mycotic infections in children receiving empirical caspofungin treatment for febrile neutropenia

Abstract: Empirical antifungal therapy is most often given to patients with leukemia. However breakthrough fungal infections under antifungal therapy are not uncommon. Four children, with hematologic malignant disease developed mycotic breakthrough infections while on empirical caspofungin treatment for a median of 14 (range 11-19) days. Trichosporon asahii was detected in the blood culture of two patients and Geotrichum capitatum in the other two (one patient also had positive cerebrospinal fluid culture). Because the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 18 publications
1
15
0
2
Order By: Relevance
“…Trichosporon species is increasingly recognized as a dangerous and opportunistic fungus in recent decades; however, pediatric cases remain uncommon . Among 16 reported species of Trichosporon , T. asahii is the most common cause of disseminated infections with little propensity for cutaneous disease .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trichosporon species is increasingly recognized as a dangerous and opportunistic fungus in recent decades; however, pediatric cases remain uncommon . Among 16 reported species of Trichosporon , T. asahii is the most common cause of disseminated infections with little propensity for cutaneous disease .…”
Section: Discussionmentioning
confidence: 99%
“…Trichosporon species is increasingly recognized as a dangerous and opportunistic fungus in recent decades 1 ; however, pediatric cases remain uncommon. [5][6][7][8][9][10][11][12] Among 16 reported species of Trichosporon, T. asahii is the most common cause of disseminated infections with little propensity for cutaneous disease. 1 The progression of superficial infection with T. asahii to deeper-set tissue involvement has been described, 1 and our case would suggest that skin involvement can also arise in the setting of therapy for invasive disease.…”
Section: Discussionmentioning
confidence: 99%
“…They have been involved in a variety of opportunistic infections and have been recognised as emerging fungal pathogens in immunocompromised hosts . Studies also indicated that T. asahii , T. asteroids , T. cutaneum , T. faecale , T. inkin , T. mucoides or T. ovoides are involved in hypersensitivity pneumonitis, pulmonary infections and superficial infections, sinusitis, fungaemia, in HIV patients, a bone marrow transplant recipient, a solid organ transplant recipient and in a patient with severe aplastic anaemia . Members of the genus Trichosporon have occasionally been implicated as nail pathogens and in subcutaneous infections .…”
Section: Resultsmentioning
confidence: 99%
“…This finding suggests that in vitro and in vivo activity of antifungals may differ. There are several publications on cases of infections in patients receiving echinocandins (caspofungin and micafungin) [7], [15], [16]. The removal of central venous catheter also seems to be an important aspect of treatment, as removal was shown as a prognostic indicator for success in one study [6].…”
Section: Discussionmentioning
confidence: 99%